CHALLENGES AND SOLUTIONS IN IMPLEMENTING THE INDEPENDENT CURRICULUM - Yusroh Jalil (LENTERA ANAK, 2025)
Challenges and solutions in implementing an independent curriculum at RA AL-WAHDAH. This study aims to find out "Implementing an independent curriculum at RA AL-WAHDAH". The type of research used is descriptive qualitative research by conducting a literaturereview on the implementation of an independent curriculum in PAUD, Data collection is carried outusing primary data in the form of survey questionnaires and direct observation data in the field byusing observation and conducting direct interviews with the principal of RA Al-Wahdah Sumber andobserving learning activities in the classroom. The results of the research and the results of thediscussion can be seen that using the Merdeka Curriculum at the PAUD level, especially with regardto resources, differences in child development, and teacher adjustment to the new curriculum. Thecase study at RA Al-Wahdah shows various steps to overcome these challenges, such as utilizing thesurrounding environment, teacher creativity, and collaboration with parents. The conclusion of thisstudy is that the Implementation of Merdeka Curriculum at RA Al-Wahdah supports early childhooddevelopment with a pleasant learning atmosphere. Cooperation with the community and teacherinnovation are the keys to success. Children are involved in active learning and developmentalevaluations are carried out regularly.